THE MORALITY AND LEGALITY OF BAR DANCING IN SONIA FALEIRO’S BEAUTIFUL THINGS - K.P. Bakhya Seema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sonia Faleiro’s writings are non-fictional and quasi anthropological cum literary writings on bar dancers. She introduces bar dancer’s world of profession by her writings. Intense involvement of love, sex, violence of customers and gangsters, of police, prostitutes and pimps are portrayed by Sonia Faleiro in her book Beautiful Things. These personalities are in one way or other involved in the profession and the difference is one spends money for pleasure and some one spends or earn money for their livelihood. what forces there adolescent girls to become bar dancers? Is it poverty or illiteracy or independence? Is the morality of bar dancing judged objectively, using same criteria that are applied to other professions too? Or is it simply immoral and highly unethical. It is a big question to be asked and judged about. The paper concentrates on these issues in the light of legal enactment and literary writing on this issue.